A field study on the oviposition of Ostrinia furnacalis Guenee (Lepidoptera: Pyralidae) on maize in Selangor, Malaysia - Hussein, M.Y.; Kameldeer, A.K. (Taylor & Francis, 1988)
A field study on the oviposition of Ostrinia furnacalis and plant growth stage, plant height, rainfall and larval density at Universiti Pertanian Malaysia, Serdang showed that in the field 74% of adult moths preferred to oviposit on the middle leaves as compared to other parts of the plants. Nearly twice as many eggs were oviposited on the lower leaf surface (63%) as compared to the upper (37%). The mid-whorl and tassel stages were most attractive to adults of generation 1 and 2, respectively. Oviposition was related to plant height, but plants over 200 cm were not preferred. The number of bored holes was a significant predictor of larval density but not egg numbers. Rainfall may be important in influencing moth activity and oviposition, particularly significant in generation 2. The use of this data in planning and timing insecticide application is discussed.